Z dziejów seminariów warszawskich w dawnej diecezji poznańskiej. Biskupi oraz inni przedstawiciele znamienitych rodów doby staropolskiej w gronie wychowanków seminarium externum i seminarium internum Misjonarzy św. Wincentego à Paulo przy kościele Świętego Krzyża w Warszawie (1675/1676-1864/1865) - Prokop, Krzysztof R. (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
Until 1798 Warsaw remained in the diocese of Poznań despite taking over from Cracow numerous functions of a capital city in the 17th and 18th centuries (nominally it never became the capital of the Polish-Lithuanian Commonwealth). During this time two seminaries ran by the Missionaries of St. Vincent de Paul functioned in Warsaw: Seminarium Internum and Seminarium Externum. They were founded in 1675-1676 and educated – especially the latter one – a large group of clergy who later held prominent positions in the structures of the Catholic Church on Polish-Lithuanian-Ruthenian soil. Among the seminary’s graduates were 66 future bishops (only eight of them underwent formation in Seminarium Internum), who were to minister as ordinaries or suffragans in a majority of dioceses then existing within the borders of the Kingdom of Poland and the Grand Duchy of Lithuania (and also on the territory of historical Greater Poland). Both of the above mentioned theological institutes located in Warsaw continued to function for some decades after the collapse of the pre-partition Polish-Lithuanian state (by then already within the Warsaw diocese and from 1818 in the Warsaw archdiocese). Their existence came to an end in 1864 as a result of repressions by Russian administration after the collapse of the January Uprising. In this second period of the seminaries’ operation the number of alumni who later filled episcopal offices was markedly lower, the last one being the future Gniezno-Poznań metropolitan and cardinal, Mieczysław Ledóchowski, whose name stands out illustriously in the history of the Church in Greater Poland.